Neutralization of SARS-CoV-2 pseudovirus using ACE2-engineered extracellular vesicles - Wu, Canhao; Xu, Qin; Wang, Huiyuan; Tu, Bin; Zeng, Jiaxin; Zhao, Pengfei; Shi, Mingjie; Qiu, Hong; Huang, Yongzhuo (Acta pharmaceutica Sinica. B, 2022)
The spread of coronavirus disease 2019 (COVID-19) throughout the world has resulted in stressful healthcare burdens and global health crises. Developing an effective measure to protect people from infection is an urgent need. The blockage of interaction between angiotensin-converting enzyme 2 (ACE2) and S protein is considered an essential target for anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) drugs. A full-length ACE2 protein could be a potential drug to block early entry of SARS-CoV-2 into host cells. In this study, a therapeutic strategy was developed by using extracellular vesicles (EVs) with decoy receptor ACE2 for neutralization of SARS-CoV-2. The EVs embedded with engineered ACE2 (EVs-ACE2) were prepared; the EVs-ACE2 were derived from an engineered cell line with stable ACE2 expression. The potential effect of the EVs-ACE2 on anti-SARS-CoV-2 was demonstrated by both in vitro and in vivo neutralization experiments using the pseudovirus with the S protein (S-pseudovirus). EVs-ACE2 can inhibit the infection of S-pseudovirus in various cells, and importantly, the mice treated with intranasal administration of EVs-ACE2 can suppress the entry of S-pseudovirus into the mucosal epithelium. Therefore, the intranasal EVs-ACE2 could be a preventive medicine to protect from SARS-CoV-2 infection. This EVs-based strategy offers a potential route to COVID-19 drug development. Extracellular vesicles (EVs) embedded with engineered ACE2 can inhibit the transfection of S-pseudovirus in the host cells by serving as decoy receptors and competitively binding with the virus. [Display omitted]